A multiphysics model for charged liquid droplet breakup in electric fields. (April 2017) - Du, Wenbo; Chaudhuri, Santanu
Highlights: Multiphysics model couples multiphase flow, charged species transport, and electrostatics. Simulations show charged droplets formed from Rayleigh breakup of axisymmetric jets. Effects of electric potential, surface tension, viscosity, and mobility are analyzed. Distribution of droplet size and velocity are quantified with respect to electric potential. Charge and mass of droplets are compared to experimental literature. Abstract: A computational multiphysics model for simulating the formation and breakup of droplets from axisymmetric charged liquid jets in electric fields is developed. A fully-coupled approach is used to combine two-phase flow, electrostatics, and transport of charged species via diffusion, convection, and migration. A conservative level-set method is shown to be robust and efficient for interface tracking. Parametric simulations are performed across a range of fluid properties corresponding to commonly used liquids in inkjet printing and spray applications to examine their role in jet evolution and droplet formation. Specifically, the effects of electric potential drop, surface tension, viscosity, and mobility are investigated. Droplet velocity and size distributions are calculated, and the corresponding mean values are found to increase and decrease respectively with increasing electric field strength. The variations in droplet velocity and size are quantified, and droplet size and charge levels agree well with experimental values. Increasing mobility of charged species is found to enhance jet velocity and accelerate droplet formation by shifting charge from the liquid interior to the interface.